Analisis Kesalahan Siswa dalam Menyelesaikan Soal Kemaritiman dengan Prosedur Newman Ditinjau dari Gender - Fadhilah Rahmawati; Nurul Aini Adiningsih; Lia Listiati; Silfiana Sulistyani; Novia Anjani; Bagas Setya Basuki (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2021)
This study aims to describe the students' mistakes and explain the factors causing the errors made by students in solving maritime problems based on the Newman procedure in terms of gender. The data were collected by means of tests and unstructured interviews. This type of research is descriptive qualitative research. The research subjects were 24 students, namely 12 male students and 12 female students. Various students’ mistakes in solving questions, including: 1) errors in reading; 2) errors in comprehension; 3) errors in transformation; 4) errors in processing skills; and 5) errors in encoding. The research results showed that there were differences in the types of errors of male and female students in solving maritime questions. The most mistakes made by students, namely errors in comprehension. From the research results, it was found that male students made more errors in compehension than female students. Male students made errors in comprehension by 63,4%, while female students made errors in comprehension by 59,2%. The research results also showed that female students made more errors in transformation, process skills, and encoding than male students.